2021
DOI: 10.7150/jca.50785
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Role and Prognostic Value of APBB1IP in Pan-Cancer Analysis

Abstract: Objective: APBB1IP is a Rap1-binding protein that mainly acts as a regulator of leukocyte recruitment and pathogen clearance through complement-mediated phagocytosis. However, the role of APBB1IP in tumor immunity remains unclear. This study was carried out to evaluate the prognostic landscape of APBB1IP in pan-cancer analysis and investigate the relationship between APBB1IP expression and immune infiltration. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Immune evasion is an important marker of cancer and has long been considered as a basic process of tumor formation and progression ( Chen and Mellman, 2017 ; Lei X. et al, 2020 ). The prognostic value of immune-infiltrating cells has been extensively studied in various malignancies, but ACSL4 has not been well studied in immuno-oncology ( Ge et al, 2021 ; Yu et al, 2021 ). A major finding in this study was that ACSL4 expression was associated with levels of immune invasion across multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Immune evasion is an important marker of cancer and has long been considered as a basic process of tumor formation and progression ( Chen and Mellman, 2017 ; Lei X. et al, 2020 ). The prognostic value of immune-infiltrating cells has been extensively studied in various malignancies, but ACSL4 has not been well studied in immuno-oncology ( Ge et al, 2021 ; Yu et al, 2021 ). A major finding in this study was that ACSL4 expression was associated with levels of immune invasion across multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the important roles of NAAA in the immune system, the correlation of NAAA function in immuno-oncology is still unknown. Here, we conducted a pan-cancer bioinformatics analysis of the expression profile and prognostic value of NAAA and explore its potential role in tumor immunology (43). We first assessed the expression and prognostic significance of NAAA in pan-cancer using the GTEx and TCGA datasets.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, oxidative stress induced obstruction of splenic arterioles, which also showed from the side that platelet activation promoted the formation of thrombus. Furthermore, as a Rap1 binding protein, APBB1IP is primarily responsible for leukocyte recruitment and pathogen clearance through complement-mediated phagocytosis (Ge et al, 2021). The spleen is an essential immunological organ that can filter out cell debris, infections and aberrant cells, as well being as a source of red and white blood cells and immune cell subtypes (Lewis et al, 2007).…”
Section: Effect Of Oxidative Stress On Platelet Activationmentioning
confidence: 99%